Sustainable conversion of waste plastics to biofuel: Process insights and fuel characteristics - Uchhwas Banik; Muhammad Nurul Huda; Mohammad Harun-Ur-Rashid; Razu Ahmmed; Md. Anowar Hosen; Mohammad Ismail (PLoS ONE, 2026)
Plastic consumption has become pervasive in modern society, with over 300 million metric tonnes produced annually worldwide, contributing significantly to municipal waste. In Bangladesh, where annual per capita plastic use has risen to 22 kg as of 2022, innovative solutions for managing plastic waste are urgently needed. This research introduces a novel approach to the pyrolysis of various plastics (PET, PVC, PP, HDPE) within a temperature range of 300 °C to 550 °C to produce pyrolytic bio-oil and biochar. We established optimal conditions for each plastic type—500 °C for PET, PVC, and HDPE, and 450 °C for PP—resulting in maximized yields of high-quality liquid oils (61.3% for PP and 47.23% for HDPE). Unique to this study, we innovatively adjust the pyrolysis process parameters to enhance the yield and quality of the derived bio-oils, tailored specifically to the types of plastics treated. The liquid products were characterized as predominantly consisting of C6–C16 hydrocarbons, aligning them closely with naphtha, gasoline, and diesel specifications, suitable for use as renewable fuels. Furthermore, our research applies FTIR and GC-MS analyses in a novel way to provide a detailed examination of these bio-oils, revealing significant quantities of paraffinic hydrocarbons in PP and olefins and naphthenes in HDPE, contributing to their potential fuel applications. The solid char byproducts were also comprehensively characterized using SEM and XRD, providing insights into their suitability for various industrial applications. This study not only demonstrates the potential of pyrolysis to transform waste plastics into valuable renewable energy resources but also advances the technological framework for sustainable waste management practices, marking a significant leap forward in the efficiency and application of plastic waste conversion technologies.